A critical survey on Cardinal Islamic practices in early Malay texts - Abdul Jalil, Mohd. Noh (2019)
Traditional Malay texts are an important heritage of the Malay world. The authors of these texts recorded and portrayed the history and life of the Malay community as they witnessed, directly or indirectly. Hence, such texts are the best available evidence for us to understand the life and religious commitment of the Malays of the bygone centuries. Thus, this study attempts to analyze the expression of Islam and Islamic practices explained in the classical Malay texts. The researchers will employ the Textual analysis method to scrutinize terms and terminologies that refer to the main pillars of Islam; namely the testimony of faith (syahadat), prayer (solat), fasting (saum), almsgiving (zakat) and pilgrimage to Mecca (haj). Very precisely, the analysis will focus on the terminology and the contextual meaning of the main pillars of Islam used in the early Malay texts. Special reference will be made to the frequency, in which these terms appear in early Malay texts as stated in the Malay Concordance Project’s database.